Teacher talks: an analysis of direct and indirect influences for young learners in EFL class - Indriyani, Christina Eli; Trioktawiani, Fransiska Regita (LPPM Universitas Mercu Buana Yogyakarta, 2019)
This study investigated the types of teacher talks in classroom interactions; those are direct and indirect influences as proposed by Flanders (1970). Besides, the analysis of the teachers’ difficulties during their talks was found out since the subjects in this study were teacher candidates. They had been taught about teacher talk during their micro teaching and teaching practicum classes. Therefore, the proposed research questions were: 1) What are the direct and indirect influences of teacher talks for young learners that appeared in EFL class? 2) What are teacher’s difficulties during teacher talks? To answer the research questions, qualitative research was employed in this study by using observation sheet and questionnaire. The participants were five pre-service teachers from English Education Department of a private university in Jakarta. The teachers had joined teaching practicum in school so that they had had experiences in teaching primary school students. Based on the result, indirect influence of teacher talk were more frequently used (59%). Teachers indirectly influences the students by asking questions. Meanwhile, the direct influence gained 41% of the whole teacher talks with giving direction as the highest frequency (30%). Furthermore, vocabulary and grammar became the main factors of difficulty in teacher talk. Teachers sometimes got confused on how to deliver the certain expressions or give instructions, which made them less confident, especially when they felt nervous. This study was hopefully beneficial for the English department and universities to provide better learning process, other teachers’ candidates that still improve their speaking skills to be more aware of their talks during teaching, and future researchers to broaden the field of study.